Draft Genome Sequences of Two Multidrug-Resistant Acinetobacter baumannii Strains of Sequence Type ST92 and ST96 - Ho, Alex Y. M. (American Society for Microbiology, 2013)
The global epidemiology of multidrug-resistant Acinetobacter baumannii is dominated by a limited number of clones. Here, we announce the draft genome sequences of two multidrug-resistant A. baumannii strains, 1H8 and 4A3, representing the major epidemic clones, sequence type 92 (ST92) and ST96, respectively.